The Kringle V-Protease Domain Is a Fibrinogen Binding Region within Apo(a) - Xue, Song; Madison, Edwin L.; Miles, Lindsey A. (Thrombosis and Haemostasis, 2001)
Lp(a) binds directly to fibrin and competes for the interaction of plasminogen with this substrate. This competition may play a role in the proatherothrombogenic consequences of high Lp(a) levels. Previous studies by us and others showed that apo(a) Kringle IV-10 competes for the interaction of Lp(a) with plasmin-treated fibrinogen. However, kringle IV-10 cannot account for the entire high affinity interaction of Lp(a) with fibrinogen. Therefore, we tested the hypothesis that the apo(a) kringle V protease-like domain (KV-PD) could interact with plasmin-treated fibrinogen. We cloned the apo(a) KV-PD region from a human liver cDNA library. Fusion apo(a) KV-PD was expressed in COS 7 cells and purified from the conditioned media. Western blotting of the apo(a) KV-PD protein revealed two bands migrating with apparent molecular weights of 45K and 48K. When fusion apo(a) KV-PD was treated with O-glycosidase and neuraminidase, the higher molecular weight band disappeared suggesting that the apo(a) KV-PD was O-glycosylated. Apo(a) KV-PD bound to plasmin-treated fibrinogen in a dose-dependent fashion. An EC50 of 3.9 ± 0.2 μM was determined for this interaction. Treatment of the apo(a) KV-PD with O-glycosidase did not significantly affect its ability to bind to plasmin-treated fibrinogen. In addition, apo(a) KV-PD competed for the binding of 125I-Lp(a) to plasmin-treated fibrinogen. An IC50 of 7.90 ± 0.95 μM was obtained. Our data suggest that the KV-PD of apo(a) shares binding sites on plasmin-treated fibrinogen with Lp(a) and also may participate in the interaction of the Lp(a) particle with plasmin-treated fibrinogen.
Keywords: Apo(a); kringle; fibrinogen